Layanan Bimbingan Konseling Islami dalam Menangani Kecemasan Akademik Siswa di MAN 1 Tabalong - Nurhayati (An-Nafis: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2025)
Academic anxiety is one of the psychological problems commonly experienced by madrasah students and has a significant impact on their academic performance and mental well-being. At MAN 1 Tabalong, this phenomenon is evident through symptoms such as excessive fear of exams, lack of self-confidence, and emotional pressure during learning activities. This study focuses on the implementation of Islamic Guidance and Counseling services in helping students cope with academic anxiety. The objective of this research is to describe the forms of Islamic counseling applied, analyze the counselor’s strategies in addressing academic anxiety, and examine the effectiveness of spiritual approaches in the counseling process. This research employs a qualitative approach with a descriptive research type. Data were collected through observation, in-depth interviews, and documentation involving guidance counselors, students, and homeroom teachers. The findings reveal that Islamic counseling services at MAN 1 Tabalong are integrated with Islamic values such as patience (sabr), reliance on God (tawakkal), remembrance (dzikr), and the recitation of Qur’anic verses as a form of spiritual therapy. The counseling strategies include individual and group approaches that emphasize self-concept strengthening and inner calmness. The study concludes that Islamic guidance and counseling services are effective in helping students manage academic anxiety while also shaping religious character that enables them to face academic pressures in a healthier and more productive manner.